PENERAPAN INVENTORI KOMPETENSI INTRAPERSONAL PADA CALON KONSELOR SEBAYA SISWA SMPN 10 TARAKAN - Al Kahpi; Hendra Pribadi (AMMA : Jurnal Pengabdian Masyarakat, 2022)
Intrapersonal competence is also known as people skills or soft skills. things that are seen and needed in personal, social, learning, and career development. Counseling is the right service in increasing intrapersonal competence, because intrapersonal competence relates to psychological aspects, while the essence of counseling is psychological (Erhamwilda, 2015). The application of an inventory of intrapersonal competencies is expected to provide awareness in self-understanding so that it triggers the soft skills of students as potential peer counselors in the school environment. Understanding the diverse development of students at SMP N 10 Tarakan is an effort to build guidance and counseling in dealing with personal, social, academic, and career problems at SMP N 10 Tarakan. Based on the initial identification carried out by the implementer at SMP N 10 Tarakan, it can be concluded that there are personal problems, academic problems, social problems, and career problems. In paying attention to the identification of student problems who became respondents, the largest percentage experienced academic problems about managing study time (68.57%) and learning assignments (37.14%). In knowing the student's condition, problem data has been collected which has been made by the Guidance and Counseling teacher at SMPN 10 Tarakan. The various problems above regarding the level of intrapersonal competence, such as time management in self-regulation is an indication of intrapersonal, having uncontrolled aggressive behavior is also an indication of intrapersonal competence. This problem got the attention of the school and triggered the extra help of counseling services. This partnership program contributes to "Implementation of the Inventory of Intrapersonal Competencies in Prospective Peer Counselors of SMP N 10 Tarakan". Community preparation in facing the era of globalization and free trade, especially awareness to train soft skills through intrapersonal competence can improve themselves, so as to build interpersonal competence to prepare themselves in the future. Keywords: Intrapersonal Competence, Peer Counseling, Guidance and Counseling